2020
DOI: 10.3390/ceramics3020023
|View full text |Cite
|
Sign up to set email alerts
|

Iron (III) Oxide-Based Ceramic Material for Radiation Shielding

Abstract: We developed a new ceramic from raw material mainly composed of iron (III) oxide. The measured attenuation coefficient of the ceramic for high-energy gamma rays was in the range 0.268–0.355, which is approximately 40% of that of lead and twice that of concrete. The measured penetrating dose of the ceramic is half of that of concrete. Thus, the novel ceramic material named RASHIX may serve as a novel ceramic alternative for the wide variety of radiation shielding materials used in construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…This high Fe 2 O 3 additive ratio also resulted in a significant rise in the density of samples 4 and 5, thus contributing to the sample number 5's highest density value (i.e., 2.7184±0.0008 g cm −3 ). Similar findings have been reported in the literature, where varying the Fe 2 O 3 level had a noticeable influence on material density as well as radiation shielding properties [44,45]. One of the most important parameters attributed to the materials used in radiation fields is the half value thickness.…”
Section: Radiation Shielding Characteristicssupporting
confidence: 89%
“…This high Fe 2 O 3 additive ratio also resulted in a significant rise in the density of samples 4 and 5, thus contributing to the sample number 5's highest density value (i.e., 2.7184±0.0008 g cm −3 ). Similar findings have been reported in the literature, where varying the Fe 2 O 3 level had a noticeable influence on material density as well as radiation shielding properties [44,45]. One of the most important parameters attributed to the materials used in radiation fields is the half value thickness.…”
Section: Radiation Shielding Characteristicssupporting
confidence: 89%
“…The ceramic products used in this study were produced by the previously reported procedure, whose main ingredient is iron (III) oxide. 6) A brief description of how to make it is given below. A powder containing 99% iron oxide was fabricated into specimens by pressing gently into an iron mold, and then it was pushed and hardened with 3 MPa/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Other details related to sample preparation are referred to our previous report. 6) To investigate the shielding ability, plate-like samples of 1 cm in thickness and 10 cm in height and width were prepared, and the required number of plates were piled on top of each other. Controls for the shielding ability evaluation experiments were lead and iron plates of the same shape and a piece of concrete of 5 cm in thickness, 10 cm in height and width (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron and/or iron oxide as fillers incorporated into various composites for radiation shielding were investigated in different studies. The results indicated that the attenuation capacity of the prepared composites was enhanced compared with the traditional shielding materials [2,[48][49][50][51][52]. Aluminum and/or aluminum oxide have been investigated as fillers to improve the mechanical properties and radiation shielding effectiveness for different matrix composites.…”
Section: Introductionmentioning
confidence: 99%